Estimation and characterization of bean seed demand in Angonia district of Mozambique - Maereka, Enock Kuziwa; Makate, C.; Chataika, B.Y.; Mango, Nelson; Zulu, Rodah M.; Munthali, G.; Amane, M.I.; Chirwa, R.M. (2015)
This report highlights findings of a study that was carried out to characterize and estimate the demand for common bean seed in Angonia District of Tete Province in Mozambique. The study gathered information on the area planted to the common bean annually, engaged key informants and surveyed of 332 households in eight Localidades between April and May 2015. According to the study, 99.7 % heads of households depend on agriculture as the main occupation; working on average family farm size of 1.4 ha, often augmented with 0.06 ha available through leasing annually. In addition to family-owned farms, husbands and wives solely own 30% and 26% respectively. The main crops grown in Angonia District in descending order of prevalence, were maize (97%) common bean (94%), soybean (59%) and groundnut (45%). Other crops grown included Irish potato, cowpea and tobacco. The common bean has a long history of cultivation in the district; mean bean production experience of participating farmers was 16 years.